2000
DOI: 10.1038/35016535
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the fracture toughness of the shell of the conch Strombus gigas

Abstract: Natural composite materials are renowned for their mechanical strength and toughness: despite being highly mineralized, with the organic component constituting not more than a few per cent of the composite material, the fracture toughness exceeds that of single crystals of the pure mineral by two to three orders of magnitude. The judicious placement of the organic matrix, relative to the mineral phase, and the hierarchical structural architecture extending over several distinct length scales both play crucial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
457
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 651 publications
(485 citation statements)
references
References 8 publications
8
457
0
2
Order By: Relevance
“…This growth has been shown to depend strongly on both nutrient availability and ambient environmental conditions [101]. At quasi-static loading rates in compression, the shells of abalone [66,97,102,103], conch [104,105] and giant clam [96] employ a variety of toughening mechanisms, realized through the brick-and-mortar structure of their nacre, including crack deflection and microbuckling of the calcium carbonate plates to induce a gradual "graceful failure." These toughening mechanisms are imaged in Fig.…”
Section: Mollusk Shellsmentioning
confidence: 99%
“…This growth has been shown to depend strongly on both nutrient availability and ambient environmental conditions [101]. At quasi-static loading rates in compression, the shells of abalone [66,97,102,103], conch [104,105] and giant clam [96] employ a variety of toughening mechanisms, realized through the brick-and-mortar structure of their nacre, including crack deflection and microbuckling of the calcium carbonate plates to induce a gradual "graceful failure." These toughening mechanisms are imaged in Fig.…”
Section: Mollusk Shellsmentioning
confidence: 99%
“…These structural biological materials are sophisticated hierarchical composites based on brittle minerals and ductile polymers, which can exhibit mechanical properties that are far beyond those that can be achieved using the same synthetic compounds (Meyers et al 2008a). In particular, the principles of biologically controlled self-assembly in seashells have generated much recent interest (Jackson et al 1988;Kamat et al 2000;Evans et al 2001;Wang et al 2001;Rubner 2003;Mayer 2005); indeed, it has been suggested that their sophisticated structures can offer guidelines for the development of new generations of structural materials (Ortiz & Boyce 2008;Aizenberg & Fratzl 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Achatina fulica (Indonesian; bekicot) is also containing CaCO 3 in the shell with high yield (88-99%) [15]. In Indonesia, the habitat of Achatina fulica usually is in banana tree and it is consumed with special name "crispy fried bekicot".…”
Section: Introductionmentioning
confidence: 99%